2018
DOI: 10.4236/opj.2018.85014
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence and Structural Analysis of Samarium Doped TiO<sub>2</sub> Thin Films and Their Applications to Visible LEDs

Abstract: Samarium-doped anatase TiO 2 (A-TiO 2 :Sm) and rutile (R-TiO 2 :Sm) single phase thin films are fabricated by laser ablation and post-annealing at different temperatures. A-TiO 2 :Sm samples exhibit intense PL emission, whilst R-TiO 2 :Sm samples exhibit weak PL emission. The local crystal structure of Sm-dopants is investigated using X-ray absorption fine structure (XAFS) measurements. The thin films showing strong PL emission have lower crystal symmetry than the other samples, which show weak PL emission. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
(33 reference statements)
2
9
0
Order By: Relevance
“…For the emitting samples, the EXAFS fitting reveals a distortion in the bond lengths. This is consistent with our previous work, which showed the window of annealing temperatures for efficient Sm‐related emission is the range 400 to 900 °C . This indicates a low symmetry model, in which each of the F. N. N. and the S. N. N. has different bond lengths.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…For the emitting samples, the EXAFS fitting reveals a distortion in the bond lengths. This is consistent with our previous work, which showed the window of annealing temperatures for efficient Sm‐related emission is the range 400 to 900 °C . This indicates a low symmetry model, in which each of the F. N. N. and the S. N. N. has different bond lengths.…”
Section: Resultssupporting
confidence: 92%
“…Every spectrum appeared at the same peak position as the standard, indicating that Sm ions formed, in TiO 2 matrix, in the triply ionized state for all samples in the series. XAFS measurements were also carried out for other samples in R‐TiO 2 series, however as no further changes in the R‐TiO 2 samples with increased annealing temperatures was already reported, we select three different R‐TiO 2 samples for comparison with the A‐TiO 2 sample series.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TiO 2 thin films/nanostructure-based photodetectors reported so far are either of very high responsivity at the cost of a very long response time (∼10 s of seconds) or have a very low responsivity value with comparatively fast response time (∼ms). , The reason is that very high responsivity is achieved in such devices through trap-assisted photoconductive gain, which in turn makes the response time of the devices very long. To address the growing demands of fabrication of TiO 2 -based photodetectors with high detectivity/responsivity along with fast response time, some attempts have been made by doping TiO 2 with various metal ions, e.g., N, In, Y, Er, Cu, etc., and by depositing epitaxial TiO 2 on LaO and GaN crystals through magnetron sputtering, CVD, etc. , However, these are very expensive techniques. In the present work, the problems mentioned above are addressed by employing a simple yet inexpensive technique.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, rutile and anatase types of titanium oxide (TiO 2 ) thin films are the most likely candidates. In our group's previous research [9] [10] [11] [12] [13], we found that the best way to increase the luminescence derived from RE ions is to add them to anatase TiO 2 (A-TiO 2 ), and when Sm 3+ or Nd 3+ ions are added to TiO 2 , they replace the Ti sites and are incorporated into the TiO 2 matrix. According to a detailed X-ray absorption fine structure (XAFS) analysis, the difference in luminescence is explained by the change in the ligand structure of the REs when added to the rutile and anatase crystal lattices.…”
Section: Introductionmentioning
confidence: 99%